Remembrance of things to come - Marker, Chris 1921-2012 (2001)
"The latest "cine-essay" of Chris Marker is dense and demanding, a splendid reminder that his nimble, capacious mind has lost none of its agility, poetry, and power. Ostensibly a portrait of photographer Denise Bellon, focusing on the two decades between 1935 and 1955, the film leaps and backtracks, Marker-style, from subject to subject, from a family portrait of Bellon and her two daughters, Loleh and Yannick (the latter co-authored the film), to a wide-ranging history of surrealism, of the city of Paris, of French cinema and the birth of the cin"math"que, of Europe, the National Front, the Second World War and Spanish Civil War, and postwar politics and culture." [filmdienst.de]
Original: Frankreich 2001
Keywords: Film; DVD-Video